2021
DOI: 10.1101/2021.06.24.21259509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community Organizing for Indigenous People in the Philippines: A Proposed Approach

Abstract: Cognizant of the special needs of indigenous people in the Philippines, the Republic Act No. 8371 of 1997 was established to promote and protect their rights. Over the years, a number of community organizing efforts for the improvement of these communities were conducted by stakeholders from the private and public sectors. However, resistance has been reported due to poor understanding and integration of these indigenous populations' varied cultures and traditions. This study aims to describe the predominant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Specifically, Jailah et al ( 2021) have identified the following principles or domains in communities organizing mid the indigenous people in the Philippines: groundwork, indigenous capacity building, community participation and ownership, mobilization, and sustainability. The researchers have further asserted that if strictly adhered to, these principles have the potential in community organization processes among the indigenous population (Jailah et al, 2021).…”
Section: B Building Effective Ecotourism Organizationmentioning
confidence: 99%
“…Specifically, Jailah et al ( 2021) have identified the following principles or domains in communities organizing mid the indigenous people in the Philippines: groundwork, indigenous capacity building, community participation and ownership, mobilization, and sustainability. The researchers have further asserted that if strictly adhered to, these principles have the potential in community organization processes among the indigenous population (Jailah et al, 2021).…”
Section: B Building Effective Ecotourism Organizationmentioning
confidence: 99%